PEMBINAAN MANAJEMEN PELAKSANAAN IBADAH MAHDHAH DAN GHAIRU MAHDHAH PERSPEKTIF “ISI” (IBRAH SEJARAH ISLAM) PADA ANGGOTA FATAYAT NU RANTING TENGARAN DESA TENGARAN KABUPATEN SEMARANG TAHUN 2024 - Rosidi, Ayep; Priarni, Rina; Serani Dara Listiyani (Tahta Media Grup, 2024)
Every religious community will not be separated from worship. This activity is not only aimed at fulfilling religious obligations, but also as a way to bring humans closer to the Creator. In Islam itself, worship is one of the goals of human creation. To convince and remind the people of their purpose, apostles were sent and books were sent to them. Worship in Islam has two main focuses, namely Mahdah worship and Ghairu Mahdhah worship. Mahdhah worship is worship whose terms, conditions and pillars have been explained, exemplified by the Prophet Muhammad. As for worship, Ghairu Mahdhah is worship that provides the opportunity to perform ijtihad with provisions that do not conflict with the contents of the Al-Qur'an and Sunnah. Worship must be based on knowledge because worship without knowledge will only result in futility. Worship must also be based on faith/belief. Faith/belief will be gained one way by knowing the history of the order of worship. So knowledge of Islamic history related to worship is important. This service uses lecture methods and questions and answers in discussion forums among members of the Fatayat NU Ranting Tengaran organization, Tengaran Village, Semarang Regency. With this service, it is hoped that the public will be able to understand the management of mahdhah worship and the ghiru mahdhah perspective from the